Examining the effect of stock market development on economic growth in Thailand - Muhammad Sodbir Hamzah; Hussin Abdullah; Mohamad Shukri Abdul Hamid (Penerbit Universiti Kebangsaan Malaysia, 2020)
Thailand's stock market is considered a fast-emerging market in Asian. Previous studies indicate that the stock market (SM) in Thailand plays a vital role in boosting the economy. However, initial studies suggest that per capita GDP growth and liquidity of the stock market development (SMD) are fluctuating and the gap is very big. This study examines the impact of SMD on Economic Growth (EG) in Thailand. The indicators used for SMD are stock turnover ratio (STO) and the total value of the traded stock (TVS). EG is measured using per capita gross domestic product (GDPC). Also, two macroeconomic variables are included, which is the inflation rate and the real interest rate. A time-series data from 1985 to 2018 is used and analyzed using the autoregressive distributed lag (ARDL) bound testing approach to cointegration as well as error correction model. The findings indicate that the impact of SMD is significant on EG. STO and TVS are statistically significant in the long run but the effect for STO and TVS is positive and TVS is negative. In the short run, all indicators are not significant. So, the findings show that by increasing STO, SMD and EG will also increase. Further research is needed to look at the effect of the legal system and macroeconomic policies in Thailand as well as its effect on SMD.